Fishers Buddy - An Android and ODK based Mobile Application for Fishermen Safety - Jebaraj, Ryan; Fernandez, Rufina; Sarah, Beryl (International Journal of Computer Sciences and Engineering, 2025)
The cyclone Ockhi of the recent past which devastated the fishing community of Tamilnadu and Kerala brought into focus the fact that till date there is no set mechanism to track fishermen stranded in the sea specially during emergencies such as cyclones. Many fishermen were missing and the rescue teams had no information that could be used to track or search for the missing fishermen. Currently the only way of tracking the fishermen in Tamilnadu are the tokens distributed for fuel subsidy to boats registered with the State Government. The precautionary measures the fishermen could take to provide locational information to facilitate tracking during emergencies like cyclone need to be addressed immediately. It is towards this end, the “FISHERS BUDDY” is developed using the Open Data Kit which is an android based multiform data collection tool incorporating form data, GPS tags, photos, videos files etc. The aim of the paper is to present a prototype frame work built using smart phones and available technologies to address fishermen safety and aid rescue efforts during emergencies such as cyclones.